Multiple respiratory complications in a patient with Charcot-Marie-Tooth disease with MFN2 mutation. (2022) - Sano, Tomoya; Miyata, Jun; Matsukida, Akira; Watanabe, Chie; Suematsu, Ryohei; Tagami, Yoichi; Kimizuka, Yoshifumi; Fujikura, Yuji; Kawana, Akihiko
Abstract: Charcot-Marie-Tooth disease (CMT) is a hereditary peripheral neuropathy characterized by progressive atrophy of distal muscles. Respiratory complications are rare. We present a case of a 49-year-old male with childhood-onset CMT bearing a genetic mutation of MFN2. He had difficulty breathing when he was 46. Imaging examination revealed complications of phrenic nerve paralysis and pneumothorax with a funnel chest. Respiratory function test demonstrated severe restrictive ventilatory impairment. Polysomnography supported the diagnosis of mild sleep apnea syndrome. Noninvasive positive pressure ventilation successfully reduced respiratory symptoms. To our knowledge, this is the first demonstration of multiple respiratory complications in a CMT patient. Highlights: Respiratory complications in Charcot-Marie-Tooth disease (CMT) are rare. This is the first report of multiple respiratory complications in a CMT patient. Non-invasive ventilation was safely introduced and effective in this case.